Selective Apoptotic Effects of Resilon and Epiphany Se: In Vitro Investigation in Cell Cultures - Ebru Hazar Bodrumlu; Emre Bodrumlu; Zafer Yazıcı (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Objective: The aim of this investigation is to examine the programmed cell death mechanism using Resilon, a root canal filling material, and Epiphany SE, a root canal sealant, in a microenvironment of cultured epithelial-like cells. Methods: Vero cells were distributed into a 24-well plate at a density of 2 x 105 cells/ml per well. Fol- lowing an incubation period of 18 hours, Resilon was applied to the cell monolayer. The monolayer was combined with Resilon and covered with a pre-warmed medium before being incubated at 37 0 C in a 5% CO2 incubator. Following this, the wells were treated with a 50% diluted eluate of Epiphany SE. Resilon and Epiphany SE were then left to incubate for 0.5, 1, 3, 6, 12, 18 and 24 hours at 37 0C. Data were analyzed in IBM SPSS V23. Statistical analysis involved determining the differences in means of the specimens using a one-way ANOVA, followed by Duncan's multiple range test to as- sess specific statistical differences across various time periods. Results: It was found that between 0 and 6 hours, it was unclear whether Resilon and Epiphany SE induce apoptosis in Vero cells. Significant differences were observed 12 hours after examination comparing both the Resilon and Epiphany SE groups to the examination time prior to 12 hours (p < 0.05). These cells decreased at 18 and 24 hours. However, necrotic cells increased at each stage of the study period. The increase in the number of necrotic cells was statistically significant at 18 and 24 hours (p < 0.05). Conclusion: It is inferred that necrosis of fibroblastic cells is caused by the cytotoxic effects of both Resilon and Epiphany SE. Hence, it can cause problems with root canal over obturation.